Implementation of Compensation in the Form of Restitution for Child Victims of the Crime of Human Trafficking: Study on the Jurisdiction of the City of Padang - Harmelia, Harmelia; Kaloko, Ilhamda Fattah; Harmain, Irfan; Intan, Dian Mustika (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Trafficking in persons is regulated in Law Number 21 of 2007 concerning eradicating the Crime of Trafficking in Persons. One form of legal protection for victims is the provision of compensation in the form of restitution. Children and women were often victims of the crime of trafficking in persons. The problem how is the application of compensation in the form of restitution to children as victims of criminal acts of trafficking in persons in the jurisdiction of the city of Padang. What are the obstacles in the application of compensation in the form of restitution to children as victims of criminal acts of trafficking in persons in the jurisdiction of the city of Padang? The study uses an empirical legal. Data collection techniques are through interviews and document studies, and data analysis is qualitative. The conclusion is the application of restitution for children who are victims of criminal acts of trafficking in persons in the jurisdiction of the city of Padang has not been optimal. The obstacle in implementing restitution for children as victims of the crime of trafficking in persons is the lack of awareness of law enforcement officers on victim protection, especially restitution, which results in the rights of the victims of criminal acts being often neglected because they tend to be law enforcement are more focused on imposing criminal charges against perpetrators.